Single‐drop microextraction technique for the determination of antibiotics in environmental water. Issue 4 (2nd January 2022) - Li, Guizhen; Row, Kyung Ho
Abstract: Growing concerns related to antibiotic residues in environmental water have encouraged the development of rapid, sensitive, and accurate analytical methods. Single‐drop microextraction has been recognized as an efficient approach for the isolation and preconcentration of several analytes from a complex sample matrix. Thus, single‐drop microextraction techniques are cost‐effective and less harmful to the environment, subscribing to green analytical chemistry principles. Herein, an overview and the current advances in single‐drop microextraction for the determination of antibiotics in environmental water are presented were included. In particular, two main approaches used to perform single‐drop microextraction (direct immersion‐single‐drop microextraction and headspace‐single‐drop microextraction) are reviewed. Furthermore, the impressive analytical features and future perspectives of single‐drop microextraction are discussed in this review.